THE EFFECT OF WORKING CAPITAL MANAGEMENT ON COMPANY FINANCIAL PERFORMANCE - Rorlen, Rorlen; Siswanto, Halim Putera; Ekadjaja, Margarita; Krisnaputra, Ariel (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to determine the effect of the company's efforts to manage working capital in improving the company financial performance. One way to operate the company's working capital properly, is by implementing the cash conversion cycle. Cash conversion cycle is a cycle of cash flow in the company which is measured by using the ratios of the Average Collection Period, Inventory Turnover, and Average Payment Period, and indirectly has an influence on the profitability of the company. The research subjects are retail companies listed on Indonesia Stock Exchange (IDX) between 2017-2020. Using double regression analysis with the EViews application, the result was obtained that the Average Collection Period (ACP) has a positive but not significant effect on financial performance. Different results were obtained from the variables of Average Payment Period (APP) and Inventory Collection Period (ICP), in which each of them has a significant and negative effect on financial performance of the company.